Age-Stratified Impact of Air Pollution on Respiratory System Hospitalizations Using DLNM: A Haze Episode Analysis - Zulkifli, Siti Wafiah Hanin Mohd; Samsudin, Humaida Banu; Majid , Noriza; Roslan, Nur Firyal (Journal of Quality Measurement and Analysis, 2026)
Air pollution is a major environmental risk factor for respiratory diseases, with its impact potentially varying across age groups and during different haze episodes. The haze phenomenon, characterized by elevated concentrations of ambient air pollutants exceeding 100 µg/m³, is associated with increased respiratory health risks in exposed populations. This study aims to investigate the age stratified lagged associations between air pollutants and respiratory system hospitalizations across three defined episodes: pre-haze, haze and post-haze, using Distributed Lag Non Linear Models (DLNM). Daily counts of respiratory system hospital admissions in Peninsular Malaysia and air pollutant concentrations (PM₁₀, SO₂, NO₂, O₃ and CO) were obtained from 2000 to 2019. The data were stratified by three age groups: children (0–14 years), working adults (15–64 years) and the elderly (65+ years). DLNM was employed to estimate the delayed and non linear effects of pollutants on respiratory system hospitalizations during the pre-haze, haze and post-haze periods. The study found that the effects of air pollutants on respiratory hospital admissions varied by age group and haze episodes. The working adults group consistently showed the highest and most prolonged risks, especially during the haze period. Children exhibited immediate but shorter effects, while the elderly experienced delayed but significant impacts, particularly from SO₂ and CO during the post-haze episode. Each pollutant showed distinct lag patterns across age groups, with relative risks (RR) indicating age and haze episodes vulnerabilities. DLNM showed varying air pollution effects across age groups and haze episodes, emphasizing the need for age targeted public health strategies.